Ionization probabilities of sputtered indium atoms under atomic and polyatomic Aum− ion bombardment. (14th March 2012) - Samartsev, A. V.; Heuser, C.; Wucher, A.
<x xml:space="preserve">Abstract</x> The ionization probability of indium atoms sputtered from a polycrystalline indium surface under bombardment with 10‐keV Aum− cluster ions was measured by comparative secondary ion and neutral time‐of‐flight (ToF) mass spectrometry. The gold projectile ion beam for time‐of‐flight spectrum acquisition was interleaved with a 5‐keV Ar+ ion beam to maintain a dynamically sputter cleaned state of the surface, thereby avoiding contamination from both residual gas adsorption as well as accumulating gold from the cluster projectile beam. It is found that under these conditions the ionization probability does not significantly change as a function of cluster projectile nuclearity, a result which is in marked contrast with similar experiments where the interleaved rare gas ion beam was not used. The comparison of both experiments reveals that in the latter case the ionization probability is strongly influenced by surface contamination. Interestingly, the magnitude of this influence seems to depend on the projectile cluster size. This finding is interpreted in terms of the change in the ejection mechanism between atomic and polyatomic projectiles leading to different average escape depths of the sputtered atoms. Copyright © 2012 John Wiley & Sons, Ltd.